1984
DOI: 10.1016/s0006-3495(84)84019-9
|View full text |Cite
|
Sign up to set email alerts
|

The source of the dispersity of gramicidin A single-channel conductances. The L X Leu5-gramicidin A analog

Abstract: The L * Leu5-gramicidin A analog has been designed, synthesized, and verified for the purpose of testing the perspective that different side-chain distributions are responsible for the dispersity of single-channel conductances. The structural analysis shows that the L * Leu5 analog would limit the possible number of side-chain distributions and that the dispersity of channel conductances would decrease. The finding is the expected decrease in less probable conductance states and the associated increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Should this conformation differ or fluctuate, the dipole orientation would vary accordingly leading to different attractions or repulsions, thus to different influences on the profile at the mouth, and possibly to different single-channel conductances. A confirmation of the role of the orientation of the tryptophans can be found in the recent observation (Urry et al 1984) of the decrease in dispersity of single-channel conductances and the increase in frequency of the most probable conducting state with respect to GA brought about by replacement of Ala 5 by the more bulky Leu residue which restricts the possible conformational fluctuations of Trp 11.…”
Section: The Effect Of the Amino-acid Side Chains On The Sodium Profilementioning
confidence: 52%
“…Should this conformation differ or fluctuate, the dipole orientation would vary accordingly leading to different attractions or repulsions, thus to different influences on the profile at the mouth, and possibly to different single-channel conductances. A confirmation of the role of the orientation of the tryptophans can be found in the recent observation (Urry et al 1984) of the decrease in dispersity of single-channel conductances and the increase in frequency of the most probable conducting state with respect to GA brought about by replacement of Ala 5 by the more bulky Leu residue which restricts the possible conformational fluctuations of Trp 11.…”
Section: The Effect Of the Amino-acid Side Chains On The Sodium Profilementioning
confidence: 52%
“…4 shows representative current traces obtained in 1 M CsCl solutions and 200 mV applied potential with gramicidin A (GA) and the four analogues that were used in this study. The L-Ala7 and L-Leu5 analogues have already been shown to have channel lifetimes and primary conductance levels similar to those of GA (Prasad et al, 1986;Urry et al, 1984a;Venkatachalam et al, 1984). The con-D-Leu-L-Ala analogue has longer channel lifetimes, as would be expected from the effect of relative membrane thickness on lifetime (see for example Hladky and Haydon, 1984).…”
Section: Resultsmentioning
confidence: 91%
“…The same final purification by HPLC was carried out for all the samples used in this study. L-Leu5-GA (Urry et al, 1984a), des-L-Val7-D-Val8-GA (Urry et al, 1984b), and L Ala7-GA (Prasad et al, 1986) were synthesized and purified as reported earlier. Con-DLeu'-L-Ala5b-GA was synthesized by the solid-phase methodology as described earlier (Prasad et al, 1982).…”
Section: Synthesis Of Gramicidin a And Selected Analoguesmentioning
confidence: 99%
“…Urry et al (1981) suggested that the position of the side chains (which radiate away from the backbonelined channel) could be the cause of decreased channel conductance. In support of this hypothesis they found a decrease in the frequency of low conductance channels for Leu5-gramicidin A, where the bulky replacement side chain was expected to reduce the freedom of other side chains (Urry et al, 1984). examined a persistent difference between two different labs in observed gramicidin mini frequency.…”
Section: Introductionmentioning
confidence: 86%